Detection of Toxoplasma gondii DNA in sera samples of mice experimentally infected - Langoni, Hélio [UNESP] (2006)
Detection of Toxoplasma gondii (T. gondii) DNA in blood can help to diagnose the disease in its acute phase; however, it must be considered that hemoglobin, present in blood, can inhibit polymerase activity, making impracticable the detection of DNA in samples. Mice were experimentally infected via oral route with ME49 and BTU2 strains cysts and RH strain tachyzoites; polymerase chain reaction was used to detect T. gondii DNA in mice sera 18, 24, 48, 96, and 192 hours post infection (PI). Toxoplama gondii DNA was detected in only one animal infected with BTU2 strain, genotype III (isolated from a dog with neurological signs) 18 hours PI. The agent's DNA was not detected in any sample of the other experimental groups. New studies must be carried out to verify the technique sensitivity in researches on this agent's genetic material using sera samples of acute-phase toxoplasmosis patients, especially in cases of immunosuppression.